Digestible Sulfur Amino Acid Requirement of Male Turkeys During the 12 to 18 Week Period - Moore, D.T.; Baker, K.; Thompson, K.; Blair, E.; Firman, J.D. (International Journal of Poultry Science, 2002)
Two floor pen trials were conducted to determine the digestible sulfur amino acid (SAA) requirement of male turkeys for the periods of 83 to 92 days and 106 to 116 days. The experiments were designed using 48 pens allowing eight treatments of six replicate pens using a randomized block design. For the 83 to 92 day period, 192 toms were sorted by weight and assigned a treatment. Digestible SAA levels ranged from 3.5 to 5.9 g/kg of diet. For the 106 to 116 day period, 144 toms were sorted by weight and assigned a treatment. Digestible SAA levels ranged from 3.0 to 5.0 g/kg of diet. These levels were obtained by titrating synthetic methionine into a low protein diet. The other synthetic amino acids were added back to the low protein diet at levels sufficient to provide growth similar to a positive control diet. The positive controls for the periods were standard corn, soybean meal, and meat meal diets based on NRC (1994) recommendations. Performance parameters measured for the trial were body weight gain and feed conversion. Parts yield of birds on the second trial were also taken with no significant differences between SAA levels found. The data were analyzed by analysis of variance followed by splined regression analysis. The digestible SAA requirements for body weight gain and feed conversion of male turkeys are 3.9 and 4.0 g/kg for the 83 to 92 day period and 3.7 and 3.4 g/kg for the 106 to 116 day period, respectively.